Improved 1000-m running performance and pacing strategy with caffeine and placebo: A balanced placebo design study - Hurst, P.; Schipof-Godart, L.; Hettinga, F.; Roelands, B.; Beedie, C. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the placebo effect of caffeine on pacing strategy and performance over 1000-m running time trials using a balanced placebo design. Methods: Eleven well-trained male middle-distance athletes performed seven 1000-m time trials (1 familiarization, 2 baseline, and 4 experimental). Experimental trials consisted of the administration of 4 randomized treatments: informed caffeine/received caffeine, informed caffeine/received placebo, informed placebo/received caffeine, and informed placebo/received placebo. Split times were recorded at 200, 400, 600, 800, and 1000 m, and peak heart rate and rating of perceived exertion were recorded at the completion of the trial. Results: Relative to baseline, participants ran faster during informed caffeine/received caffeine (d=0.42) and informed caffeine/received placebo (d=0.43). These changes were associated with an increased pace during the first half of the trial. No differences were shown in pacing or performance between baseline and the informed placebo/received caffeine (d=0.21) and informed placebo/received placebo (d=0.10). No differences were reported between treatments for peak heart rate (eta2=.084) and rating of perceived exertion (eta2=.009). Conclusions: The results indicate that the effect of believing to have ingested caffeine improved performance to the same magnitude as actually receiving caffeine. These improvements were associated with an increase in pace during the first half of the time trial.